3D-DYNAMIC ANALYSIS AND DESIGN OF Al-Motamayyezoon Building IN NABLUS - Tariq M. Thawabi; Ameed S. Surakji; Adel S. Sabbah (My University, 2017)
Our Project is a commercial compound located in Rafidia Main Street, which is a very active area in Nablus, thats why we think that this project is important since it will provide more activity to Rafidia.           Al- Motamayyezon Building is a 7 floors Building considering the ground floor , in addition to  Two  more  basement floors . The Compound will involve Exhibitions especially Furniture Exhibitions , Apartments for rent and a Coffee shop at the roof. There will be garages at the basement floors.           In this project we will be using the Ultimate Design Method for Designing which is much conservative , and the International Building Code ( UBC-97 ) for design ,and the American Concrete Institute's Code (ACI-318) for Concrete structures' specifications . In this project we included a detailed design of all structural elements in the building such as slabs, beams, columns and footings. Furthermore, a 3D-designed model for the whole building and a dynamic analysis was done in order to study the behavior under earthquake.           This graduation project will be our start point towards the real world of civil engineering, and by hard work and teamwork we believe that we can make something creative.

- .              7 . . .                ((Ultimate Design Method (UBC-97) (ACI-318) .     . .
3D-DYNAMIC ANALYSIS AND DESIGN OF Al-Motamayyezoon Building IN NABLUS